The structural organization of the adjacent vertebral segments in cases of the introduction of implants, made of different biomaterials, into the interbody gap of the lumbar spine (an experimental study) - Fedak, Volodymyr; Dedukh, Ninel; Malyshkina, Svitlana (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2009)
The study was conducted on 6 rabbits of the chinchilla breed that underwent an introduction of implants, made of porous corundum ceramics and titanium, into the interbody gap at the level of LIII-LIV. It was revealed that the implantation of endoprostheses, made of biomaterials, into the interbody gap caused the development of dystrophic and destructive changes in all the components of the adjacent segments three months later. The expressiveness of the disturbances depended upon the material of the endoprosthesis, the level of the adjacent segment localization and the structural component of the segment. In cases when the titanium specimen was used, destructive changes prevailed in all the components of the adjacent segments, but manifested themselves in the caudal adjacent segments, to a larger extent in the internal parts of the fibrous ring and the pulpy nucleus of intervertebral disks. A tendency to a lower height of the caudally located intervertebral disk was observed.